(untitled) (European Journal of Education and Psychology, 2018)
The Peer Conflict Scale is a scale used for the evaluation and quantification of aggression in different forms of expression, as well as the hidden motives behind this type of behaviour. Therefore, in view of the need for a combined evaluation of the different ways in which aggression is manifested in adolescents, this study was carried out to validate the Spanish version of the Peer Conflict Scale. A sample of 822 secondary school students aged 13 to 18 was used for this. Three possible models were analysed for this scale: a one-dimensional model, a model with two types of aggression, physical and relational, and a third with four types of aggression (physical reactive aggression, relational reactive aggression, physical pro-active aggression, and relational pro-active aggression). The last is the model which shows the best fit, and therefore, is the one applied to the Spanish adolescent population.